Extracorporeal Membrane Oxygenation Incidence, Characteristics, and Outcomes in Neonatal Down Syndrome Patients. Issue 4 (July 2016) - Backes, Carl H.; Nicholson, Lisa; Rivera, Brian K.; Swier, Natasha; Marshall, William; Cua, Clifford L.
Abstract : Practice patterns for extracorporeal membrane oxygenation (ECMO) use in newborns with Trisomy 21 (T21) have not been fully reported. The goals of this study were to 1) determine the incidence of ECMO use in T21 neonates; 2) identify clinical and demographic characteristics associated with ECMO use in this population; 3) describe outcomes of neonates with T21 supported with ECMO. This was a retrospective cohort study using the Pediatric Health Information System database (January 2000 to January 2014). Given the exploratory nature, only descriptive statistics were used. p < 0.05 was considered significant. Within 43 pediatric hospitals, the incidence of ECMO use in neonates with T21 was 2.3% (131/5, 737). Neonates with T21 supported with ECMO were more likely to be admitted earlier; have higher birth weight, gestational age, and longer hospitalization; and have congenital diaphragmatic hernia or select cardiac anomalies versus those who did not require ECMO. T21 neonates supported with ECMO also had higher incidence of bronchopulmonary dysplasia, necrotizing enterocolitis, and mortality (unadjusted odds ratio 12.3 [95% confidence interval: 8.6–17.6]) compared with T21 neonates not exposed to ECMO. Compared with T21 neonates not requiring ECMO, those supported with ECMO had increased morbidity and mortality. Additional investigation on timing, indications, and risk/benefit profiles, for ECMO use in T21 neonates is needed.